Experts animated by the cinema. The cinema as an educational tool - Ruiz Vallejos, Fernando Federico (2016)
This article has been prepared based on the research “Pedagogical Perception of Cartoons: The Case of Primary School Teachers in State Schools in Metropolitan Lima”. This research has been carried out within the framework of activities performed by the Scientific Research Institute of the University of Lima during the 2014-2015 period; its first part was presented in the city of Medellin at the XV Latin American Meeting of Faculties of Social Communication 2015 (FELAFACS, by its acronym in Spanish). This research is done as a response to the concern of knowing how the characteristics of two proposals of cartoon movies, culturally and aesthetically different, are perceived by some intellectuals from the perspective of their specialties and educational communication field.